2011
DOI: 10.1128/jvi.02396-10
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-Zoster Virus (VZV) Infection of Neurons Derived from Human Embryonic Stem Cells: Direct Demonstration of Axonal Infection, Transport of VZV, and Productive Neuronal Infection

Abstract: Study of the human neurotrophic herpesvirus varicella-zoster virus (VZV) and of its ability to infect neurons has been severely limited by strict viral human tropism and limited availability of human neurons for experimentation. Human embryonic stem cells (hESC) can be differentiated to all the cell types of the body including neurons and are therefore a potentially unlimited source of human neurons to study their interactions with human neurotropic viruses. We report here reproducible infection of hESC-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
108
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(117 citation statements)
references
References 32 publications
9
108
0
Order By: Relevance
“…These results are similar to quiescent HSV-1 in neurons obtained from adult murine trigeminal ganglia wherein RNA-seq data suggest transcription from multiple regions of the virus genome in addition to LAT (Harkness et al, 2014). As the neurons can be maintained in compartmented microfluidic chambers that orientate neurite outgrowth, infection of axons with fluorescently tagged virus permits direct viewing of retrograde transport to neuronal cell bodies (Markus et al, 2011;Grigoryan et al, 2012). These nearpure (w95 % bIII-tubulin expressing) neuronal cultures provide an excellent opportunity to observe the outcome of VZV infection, such as induction of host anti-apoptotic genes (Markus et al, 2014), although latency (long-term presence of VZV DNA with limited transcription) has not yet been obtained.…”
Section: Alphaherpesvirus Gene Transcription Is Deregulated During VIsupporting
confidence: 73%
See 1 more Smart Citation
“…These results are similar to quiescent HSV-1 in neurons obtained from adult murine trigeminal ganglia wherein RNA-seq data suggest transcription from multiple regions of the virus genome in addition to LAT (Harkness et al, 2014). As the neurons can be maintained in compartmented microfluidic chambers that orientate neurite outgrowth, infection of axons with fluorescently tagged virus permits direct viewing of retrograde transport to neuronal cell bodies (Markus et al, 2011;Grigoryan et al, 2012). These nearpure (w95 % bIII-tubulin expressing) neuronal cultures provide an excellent opportunity to observe the outcome of VZV infection, such as induction of host anti-apoptotic genes (Markus et al, 2014), although latency (long-term presence of VZV DNA with limited transcription) has not yet been obtained.…”
Section: Alphaherpesvirus Gene Transcription Is Deregulated During VIsupporting
confidence: 73%
“…During primary infection, both viruses gain access to neurons most likely through retrograde transport from the site of cutaneous lesion (Topp et al, 1994). Whilst there is no conclusive evidence showing virus accessing ganglia via retrograde axonal transport from cutaneous lesions in humans, retrograde axonal transport is supported by infectious virus in cutaneous vesicles (Grose & Brunel, 1978), virus-infected neurons in the region (Chen et al, 2004), and HSV-1 and VZV retrograde axonal transport in vitro (Antinone & Smith, 2010;Markus et al, 2011). VZV is also thought to enter ganglia haematogenously.…”
Section: Introductionmentioning
confidence: 99%
“…Later studies in which VZV-infected human fetal fibroblasts were cocultivated with explanted human fetal dorsal root ganglia indicated that neurons were resistant to apoptosis (4). Recently, heterogeneous cultures derived from human embryonic stem cells that contained neurons were infected with VZV, but again productive infection ensued, presumably due to the presence of a significant proportion of nonneuronal cells (5). When differentiated human neural stem cells that were Ͼ90% neurons based on immunostaining were infected with VZV, no cytopathic effect developed, and VZV DNA, virus-specific transcripts, and proteins were detected in healthy-appearing neurons (6).…”
mentioning
confidence: 99%
“…Synaptophysin and chromogranin A puncta were still readily observed along the lengths of the axons within our study, illustrating that the functionality of TGN secretory pathways was at least partly retained. Although a model of VZV retrograde transport has recently been reported (22,32), a model assessing anterograde spread of virus still remains in developmental stages. Thus, development of more- assessed by dual-immunofluorescence staining.…”
Section: Discussionmentioning
confidence: 99%
“…VZV infections of differentiated human neural stem cells (19) and terminally differentiated neurons derived from induced pluripotent stem cells (20,21) have been reported as persistent models of VZV infection. In contrast, human embryonic stem cell (22) and differentiated human neuroblastoma (23)-derived neuronal cells induced productive VZV infection under the study conditions utilized. The differentiated SH-SY5Y neuroblastoma cell culture model previously developed by our laboratory may be particularly useful to assess the neurovirulence of VZV deletion strains or mutant strains during productive VZV infection (23).…”
mentioning
confidence: 96%